Early Christianity in the Lycus Valley Early Christianity in the Lycus Valley - Huttner, Ulrich 1965- (Leiden BRILL, 2013)
With Early Christianity in the Lycus Valley Ulrich Huttner offers a microstudy of Christian history in southwestern Asia Minor (first to fifth century C.E.).
Intro -- Contents -- Abbreviations -- Translation of Source Texts -- List of Illustrations -- Acknowledgements -- Chapter One. Introduction -- 1.1. Starting Points -- 1.1.1. Sources and Chronological Framework -- 1.1.2. Questions: Community Formation and the Search for a Position -- 1.2. History of Research -- 1.2.1. Fundamentals, Surveys, Conclusions -- 1.2.2. Epigraphy and Archaeology -- 1.2.3. Archaeological Perspectives -- 1.2.4. Theology -- 1.3. Geography and Natural Resources -- 1.3.1. Basic Geography -- 1.3.2. Infrastructure -- 1.3.3. Agriculture and Textile Production -- 1.3.4. Building Trades and Technologies -- 1.3.5. Settlement Geography I: Carura, Attouda, Trapezopolis, Tripolis -- 1.3.6. Settlement Geography II: Laodicea, Hierapolis, Colossae -- Chapter Two. Historical Background -- 2.1. Cultural and Social Background: Identities and Associations -- 2.2. Political Background -- 2.2.1. Colossae in the "Early Period -- 2.2.2. The Lycus Valley in the Hellenistic Period: New Foundations and Political Changes -- 2.2.3. Laodicea as a Central City of the Roman Province -- 2.3. Indigenous and Greek Cults -- 2.3.1. Cults of Zeus -- 2.3.2. Cults of Apollo -- 2.3.3. The Sanctuary of Lairbenos -- 2.3.4. Men -- 2.3.5. The Mother of the Gods -- 2.3.6. The Hellenistic Ruler Cult -- 2.3.7. The Roman Emperor Cult -- 2.4. Jewish Communities -- 2.4.1. Judaism in the Lycus Valley: The Beginnings -- 2.4.2. Laodicea as a Jewish Center -- 2.4.3. Conflicts between Jews and Greeks -- 2.4.4. Symbiosis of Jews and Greeks in the Imperial Period -- Chapter Three. Pauline Influence: Philemon and Colossians -- 3.1. Persons and Networks -- 3.1.1. Paul's Journeys in Asia Minor -- 3.1.2. The Prosopography of Philemon and Colossians -- 3.1.3. The Network of Churches and the Epistle to the Laodiceans -- 3.1.4. Nympha of Laodicea.
Description based on publisher supplied metadata and other sources
Keywords: Church history ; Primitive and early church, ca. 30-600; Turkey ; Church history; Electronic books